Structural and mechanical characterization of Bi1.75Pb0.25Sr2Ca2Cu3−xSnxO10+y superconductor ceramics using Vickers microhardness test - Cavdar, Şükrü; Arslan, Ayten; Koralay, Haluk; Tasci, A. T.; Gunen, A.; Asikuzun, E.; Ozturk, O. (Springer Science and Business Media LLC, 2013)
In this work we investigated the role of Sn doping on mechanical and structural properties of Bi1.75Pb0.25Sr2Ca2Cu3−xSnxO10+y (x = 0.0, 0.1, 0.3 and 0.5) superconducting ceramic material. All samples were fabricated with glass ceramic method. The prepared samples were characterized by using scanning electron microscope (SEM), energy dispersive spectroscopy (EDS), X-ray powder diffractometer (XRD) and static microhardness indenter. Surface morphology, orientation of grains, and elemental composition analysis of the samples were made by SEM and EDS measurements, respectively. Texturing and lattice parameters a and c were determined by XRD measurements. Load dependent and load independent microhardness, elastic modulus, yield strength and fracture toughness were obtained by hardness measurements. In this work we focused on Vickers microhardness measurements in order to characterize the mechanical properties of our samples. Experimental results of Vickers microhardness measurements were analyzed by using Meyer’s law, the elastic/plastic deformation model, proportional sample resistance model (PSR), modified PSR model and Hays-Kendall (HK) approach. From these analyses, HK approach was determined as the most successful model describing the mechanical properties of our samples. Finally in this study, the changes on the mechanical and microstructural properties of Sn doped Bi-2223 superconductors and their possible reasons were also discussed in detail.